Reducing the Divorce Rate in the Religious Courts Through Cultivating Egalitarian Relationships - Ulin Na’mah; Mochammad Agus Rachmatulloh; Husnul Yaqin; Rezki Suci Qamaria (Khazanah Hukum, 2024)
The income factor is often the reason for divorce by petition, a phenomenon of high divorce rates in Indonesia. Furthermore, this problem has resulted in various analytical results. It is very embarrassing that all these analyses tend to blame one party, namely that often, the wife is blamed without presenting writings about wise efforts to resolve relationship problems that lead to mutualism. Apart from that, previous researchers were still trapped in understanding the husband-and-wife relationship as a relationship that was nothing more than a matter of the rights and obligations of husband and wife, which were considered absolute. Even though the perspective of interdependence as something prescribed in Islam has begun to be discussed, there has been no study or offer on how to improve the pattern of interdependence in the lives of husbands and wives. This research aims to provide a practical way to create an egalitarian relationship between husband and wife by first uncovering the causes of the difficulty of implementing an egalitarian pattern in husband-and-wife relationships, which is a factor in the increase in divorce cases due to income reasons. This research uses an empirical or psychological phenomenological approach based on Gary Chapman's "Five Main Love Languages" theory. In selecting subjects, researchers used purposive sampling. Researchers conducted interviews with four ex-husband and wife couples in cases of divorce for reasons of livelihood in the jurisdiction of the Kediri City Religious Court. The result is a vacuum of emotional affection between husband and wife, which causes the wife to resist and be unable to give up her desire to fulfill household needs, a form of contextual and egalitarian role division. Instead of creating an egalitarian husband and wife relationship, the relationship ended in divorce. Thus, a sufficient husband and wife's love tank is the primary condition for carrying out their roles contextually and egalitarian.